(untitled) (Polis (Santiago), 2018)
In this article it is tried to give a synthetic vision of a subject as complex as it constitutes the personal reality of the human being. The reflection of Jacques Maritain encourages and nurtures the anthropological perspective that gives account of the conformation of men, of their own characteristics, their personal being, his unrenouncable dignity, his nerd to count on others to conform society, project himself in the specific realm of politics; and -finally- to assure, to deepen and to extend his freedom.